The flood: the Akkadian sources: a new edition, commentary, and a literary discussion - Ṿaserman, Natan (Orbis biblicus et orientalis, 2020)
The story of the primeval cataclysmic flood which wiped out all life on earth, save for one family, is found in different ancient Mesopotamian texts whence it reached the Biblical and Classical literary traditions. The present book systematically collects the earliest attestations of the myth of the Flood, namely all the cuneiform-written Akkadian sources – from the Old Babylonian to the Neo-Assyrian and Neo-Babylonian periods, including Tablet XI of the Epic of Gilgamesh –, presenting them in a new synoptic edition and English translation which are accompanied by a detailed philological commentary and an extensive literary discussion. The book also includes a complete glossary of the Akkadian sources